Risk Factors for Intrauterine Growth Restriction: 9 Years Analysis in Tertiary Care Hospital - Shrestha, Abha; Pradhan, N; Kayastha, B (Journal of BP Koirala Institute of Health Sciences, 2019)
Background: Intrauterine growth restricted (IUGR) fetuses are at higher risk of developing neonatal complications and also known to develop metabolic syndrome in adult life. So, an early antenatal detection, choosing the optimal time and method of delivery and intervention when required could minimize the risk significantly. Objective: To find out the prenatal outcome and the maternal and placental risk factors. Methods: A prospective study was conducted from January 2010 to January 2019, at a Teaching Hospital. A singleton pregnancy, above 28 weeks of gestation with clinical diagnosis of IUGR and confirmed by ultrasonography were included in the study. The statistical analysis was performed by Statistical Package of Social Sciences (SPSS) 23.0 software. Results: Maternal risk factors like low pregnancy body mass index, preeclampsia, anaemia, hypothyroidism and placental factors like retro placental hemorrhage were mainly responsible for intrauterine growth restriction. Conclusions: The early identification of risk factors and management of the same antenatal is an important issue to prevent adverse prenatal outcomes associated with IUGR.